Three new species of the genus Ischnomesus (Isopoda: Asellota: Ischnomesidae) from Brazilian deep sea - Santos-Silva, Elinai; Souza-Filho, Jesser F. (Zootaxa, 2017)
Three new species of genus Ischnomesus are described from three Brazilian sedimentary Basins: Alagoas-Sergipe, Espírito Santo and Campos. Ischnomesus hirsutus sp. nov. was found at depths between 1445 m and 3000 m in Alagoas-Sergipe Basin and Espírito Santo Basin. This species is characterized by having pereonite I with 1 pair of anterolateral small pedestal spines, pereonites I–IV with a pair of anterodorsal pedestal setae and pleotelson with lateral fields bulge Ischnomesus longiseta sp. nov. was found between 400 and 1000 m, on the upper slope in Alagoas-Sergipe Basin and Espírito Santo Basin, and is characterized by having the pereonites without spines or tubercles, but covered with long simple setae, pleotelson with 5 lateral simple setae, without spines or tubercles. Ischnomesus wilsoni sp. nov. was found on the upper slope between 750 and 830 m in Espírito Santo Basin and Campos Basin. This species has the body entirely ornamented with pedestal spines. This is the first record of the family Ischnomesidae for Brazilian waters.